A bacteriological assessment of the cleaning and disinfection efficacy at the Midlands State University canteen, Zimbabwe - Moyo, Doreen Z.; Baudi, I. (Asian Network for Scientific Information, 2016)
A bacteriological assessment of the cleaning and disinfection efficacy at the Midlands State University Canteen was done. Ten random assay visits were carried out and the total counts from various environmental surfaces were determined using the Agar Syringe method. Food quality was also determined by testing for coliforms and Salmonella. Results of the study indicated that cutting boards, vegetable-section and meat-section tables were frequently found to be the most highly contaminated surfaces. Cooked food was found to be of satisfactory microbiological quality. The maximum efficacy of the cleaning and disinfection program at the Midlands State University canteen was found to be 62% but with a high potential for improvement.